Optimasi Formula Kombucha Bunga Telang (Clitoria ternatea L.) Dalam Sediaan Sabun Mandi Cair Dengan Metode Factorial design - Agma Beladina Gita Anggara Dewi; Suprapto Suprapto (Journal of Pharmaceutical and Sciences, 2026)
Introduction: Natural-based liquid soap has gained increasing interest as a multifunctional skin cleanser with antibacterial properties. Butterfly pea flower (Clitoria ternatea L.) is rich in bioactive compounds such as flavonoids and anthocyanins that exhibit antibacterial potential, which can be enhanced through fermentation into kombucha. Objective: This study aimed to optimize the formulation of butterfly pea flower kombucha liquid soap using a factorial design method and to evaluate its physical stability and antibacterial activity against Staphylococcus aureus. Methods: Optimization was performed using a 2² factorial design with a center point assisted by Design-Expert® software, with variations in kombucha fermentation time (7, 10.5, and 14 days) and kombucha concentration (20%, 30%, and 40%). The response parameters optimized included pH, viscosity, and foam stability. The optimum formula was evaluated for physical stability using a freeze-thaw cycling method for 6 cycles and tested for antibacterial activity against S. aureus using the well diffusion method. Results: The optimum formula was obtained at a fermentation time of 10.5 days and a kombucha concentration of 20%, yielding a desirability value of 0.874. The optimized formulation exhibited a pH of 5.23 ± 0.15, viscosity of 1674.0 ± 8.76 cP, and foam stability of 73.67 ± 1.53%. Verification experiments confirmed that the observed values fell within the 95% prediction interval, validating the model. Physical stability testing demonstrated no significant changes in organoleptic properties, homogeneity, pH, viscosity, or foam stability after 6 freeze-thaw cycles. The optimum formula showed strong antibacterial activity against S. aureus with an average inhibition zone diameter of 13.67 ± 0.29 mm. Conclusion: The optimized butterfly pea kombucha liquid soap formulation possesses excellent physical characteristics, good stability, and promising potential as a natural antibacterial cleanser.